(untitled) (KIUT Publication, 2025)
Epilepsy affects a significant proportion of the population, and consistent anti‑seizure medication (ASM) usage is critical for seizure control. In Uzbekistan, challenges include limited availability of newer-generation ASMs and high out-of-pocket costs. This study examines the real-world experiences of epilepsy patients and caregivers regarding medication access, especially outside of Tashkent